ENCOURAGING STUDENTS’ MOTIVATION WITH PRAISE IN AN EFL CLASSROOM - Indrawaty Asfah (Media Inovasi Pendidikan dan Publikasi, 2023)
Encouraging motivation of students is essential to increase their performance and involvement in classroom activities. Academic performance, inappropriate behavior and unproductive classrooms are all related to motivation issues. This study aims to describe how praise can motivate students in an EFL classroom. This study used descriptive method. Data was collected through self-administered questionnaire. The results of the study indicate praise does encourage students’ motivation